2011
DOI: 10.1007/s10162-011-0283-2
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Primary Cochlear Neuronal Degeneration in Human Temporal Bones

Abstract: In cases of acquired sensorineural hearing loss, death of cochlear neurons is thought to arise largely as a result of sensory-cell loss. However, recent studies of acoustic overexposure report massive degeneration of the cochlear nerve despite complete hair cell survival (Kujawa and Liberman,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
297
2
6

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 349 publications
(329 citation statements)
references
References 32 publications
24
297
2
6
Order By: Relevance
“…In contrast, previous animal studies showed that moderate noise exposure and early aging can produce synapse/ neuronal loss without changes to cochlear mechanics and with no hair cell loss-a completely different form of sensorineural hearing loss (Kujawa and Liberman, 2009;Makary et al, 2011;Sergeyenko et al, 2013). Here, we investigated whether perceptual differences in the general population of NH listeners who have no known hearing deficits are consistent with this mechanism of synaptopathy/neuropathy (Bharadwaj et al, 2014).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…In contrast, previous animal studies showed that moderate noise exposure and early aging can produce synapse/ neuronal loss without changes to cochlear mechanics and with no hair cell loss-a completely different form of sensorineural hearing loss (Kujawa and Liberman, 2009;Makary et al, 2011;Sergeyenko et al, 2013). Here, we investigated whether perceptual differences in the general population of NH listeners who have no known hearing deficits are consistent with this mechanism of synaptopathy/neuropathy (Bharadwaj et al, 2014).…”
Section: Discussionmentioning
confidence: 68%
“…Aging also appears to reduce the effective auditory nerve fiber (ANF) population, initially through a loss of synapses with a subsequent degeneration of cell bodies (Makary et al, 2011;Sergeyenko et al, 2013). Furthermore, significant levels of deafferentation do not appear to affect detection thresholds (Schuknecht and Woellner, 1955;Lobarinas et al, 2013); however, in the healthy auditory system, convergence of nerve fibers is important for precise coding of both temporal finestructure and envelope cues in suprathreshold sounds (Joris et al, 1994;Lopez-Poveda and Barrios, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…We determined whether ribbons were associated with glutamate receptors (GluA2) or afferent terminals (Na/K-ATPase). This analysis was aided by custom software that computed and displayed the x-y projection of the voxel space within 1 m of the center of each ribbon, as identified from the Amira analysis (Liberman et al, 2011). Juxtaposed ribbons and receptors or ribbons and terminals could then be viewed (and counted) within the generated array of thumbnails.…”
Section: Histologic Preparation and Assessmentmentioning
confidence: 99%
“…They require the biological motors in OHCs , which amplify sound-evoked cochlear vibration. They do not require IHCs or auditory nerve fibers (Takeno et al, 1994;Kujawa and Liberman, 2009). ABRs are electric potentials recorded from scalp electrodes, and the first ABR wave represents the summed activity of the auditory nerve fibers contacting IHCs (Buchwald and Huang, 1975).…”
Section: Cochlear Thresholds and Suprathreshold Response Growthmentioning
confidence: 99%
See 1 more Smart Citation